Exposure of children and adolescents to alcohol advertising on Australian metropolitan free-to-air television - Fielder, Lynda; Donovan, Robert; Ouschan, Robyn (Wiley-Blackwell Publishing Ltd., 2009)
This study investigated the exposure of underage youth to alcohol television advertising on metropolitan free-to-air television in the five mainland capital city markets of Australia. Exposure levels (target audience rating points; TARPs) were obtained for all alcohol advertisements screened from November 2005 to October 2006 in each capital city market for: children 0-12 years; underage teens 13-17 years; young adults 18-24 years; and mature adults 25+ years. The thirty most exposed advertisements across age groups were then content analysed for elements appealing to children and underage youth. In each of the five metropolitan markets, mature adults were most exposed to alcohol advertising. Children were exposed to one third the level of mature adults and underage teens to approximately the same level as young adults. However there was considerable variation in media weight between markets such that underage teens in two markets had higher advertising TARPs than young adults in other markets. All thirty highest exposed advertisements contained at least one element known to appeal to children and underage youth, with 23 containing two or more such elements. Fifteen of the 30 advertisements featured an animal. The self-regulation system in Australia does not protect children and youth from exposure to alcohol advertising, much of which contains elements appealing to these groups.